OBSERVATION ASSESSMENT INDICATORS ANALYSIS IN IMPLEMENTATION “STRENGTHENING PANCASILA STUDENT PROFILES PROJECT” OF MERDEKA CURRICULUM IN ISLAMIC SCHOOL - Farwati, Ratna; Metafisika, Kartika; Herlina, Herlina; Afifah, Afifah (Proceeding of International Conference on Islamic Education (ICIED), 2022)
Faith, fear of God Almighty and noble character, global diversity, cooperation, independence, critical reasoning, and creativity are the profiles of Pancasila students that can be grown through the implementation of active and integrative learning. Each profile has key elements that have been formulated and the indicators derived in the form of elements and sub-elements. However, with many Islamic schools also adapting to an independent curriculum, the content of the sub-elements needs to be added according to the content and values of Islam. In addition, it is necessary to have a description of the indicators from the observations of the Pancasila Student Profile Strengthening Project (5P) from the Pancasila Student Profile Dimensions to make it easier for teachers to formulate project-based learning observation assessments. By using the content analysis method, indicators are formulated for assessment of observations in 5P activities derived from elements and sub-elements of the Pancasila Student Profile. This observational assessment indicator for project-based learning can be used as a guideline for assessing the implementation of project-based learning in Islamic-based schools and madrasas. With these overall skill indicators, there can be a synergy between the characteristics of project-based learning with the key elements of the Pancasila student profile as an observational assessment that can be used by all teachers in project-based learning in Islamic-based schools.